2002
DOI: 10.1007/s003300101082
|View full text |Cite
|
Sign up to set email alerts
|

Patient acceptance for CT colonography: what is the real issue?

Abstract: The aim of this study was to evaluate the discomfort associated with CT colonography compared with colonoscopy and bowel purgation cleansing, and to evaluate patient preference between CT colonography and colonoscopy. In a total of 124 patients, scheduled for multidetector virtual CT colonography and diagnostic colonoscopy, patient acceptance and future preference were assessed during the different steps of the procedure (colon preparation, CT examination, and conventional colonoscopy). Patients who described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 25 publications
3
52
2
4
Order By: Relevance
“…Inflation was sustained in accordance with the level of patient discomfort. Relief could be obtained by releasing the pressure on the bag to allow backflow of inflated air and residual preparation fluid (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflation was sustained in accordance with the level of patient discomfort. Relief could be obtained by releasing the pressure on the bag to allow backflow of inflated air and residual preparation fluid (7).…”
Section: Methodsmentioning
confidence: 99%
“…The participation rate of the target population is often neglected, even though all current techniques require a specific preparation protocol that is associated with definite discomfort for the patient (7).…”
mentioning
confidence: 99%
“…However, there have been reports about a possible correlation between nephrogenic fibrosing dermopathy (NFD) and the intravenous administration of gadolinium compounds (20). As far as patient acceptance is concerned, several trials revealed a higher acceptance rate for virtual colonography compared to optical endoscopy (21)(22)(23). The need to undergo bowel cleansing yet is rated as the most unpleasant part of the virtual colonography exam (21-25) and patient discomfort scores can be significantly improved with tagging preparations previously shown for CT colonoscopy (CTC) (26).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional colonoscopy is the gold standard method for detection of colonic pathologies (16,17). However, the method is invasive and disturbing, reducing its acceptability (18,19). Ionizing radiation exposure is an important disadvantage for CT colonography (7,8).…”
Section: Introductionmentioning
confidence: 99%